1993
DOI: 10.1002/bdd.2510140204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acetaminophen and lorazepam glucuronidation in vitro by probenecid

Abstract: The effect of probenecid on glucuronidation of acetaminophen and lorazepam in hepatic microsomes from various species was studied to see if in vitro results were consistent with previous in vivo observations. Mouse, rat, and human microsomes were incubated with acetaminophen and probenecid while monkey microsomes were incubated with lorazepam and probenecid. Glucuronidation rates in all species varied with substrate, protein, and detergent concentrations. Mice exhibited faster rates of glucuronidation than rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…A number of studies have also shown that PRB inhibits the activity of UGTs [14–21]. We have previously reported the inhibitory effect of PRB on acetaminophen and lorazepam glucuronidation in vitro and in vivo [13,22]. In this study, we did not evaluate which specific isoforms are responsible for 2ME2 glucuronidation, nor did we determine the inhibitory effect of PRB vs individual UGT isoforms.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A number of studies have also shown that PRB inhibits the activity of UGTs [14–21]. We have previously reported the inhibitory effect of PRB on acetaminophen and lorazepam glucuronidation in vitro and in vivo [13,22]. In this study, we did not evaluate which specific isoforms are responsible for 2ME2 glucuronidation, nor did we determine the inhibitory effect of PRB vs individual UGT isoforms.…”
Section: Discussionmentioning
confidence: 93%
“…Glucuronidation via UDP‐glucuronyl transferases (UGTs)[9] is considered to be the principal pathway responsible for 2ME2 metabolism [10]. Probenecid (PRB), which is mainly used for gout treatment,[11,12] is also a known inhibitor of UGTs [13–22]. Therefore, we evaluated the inhibitory effect of PRB on 2ME2 glucuronidation using an in‐vitro model of human liver microsomes (HLMs).…”
Section: Introductionmentioning
confidence: 99%
“…UGT activities using nine other marker substrates (estradiol, trifluoperazine, 4-nitrophenol, propofol, acetaminophen, azidothymidine, R-and S-oxazepam and morphine) were measured with the same set of human liver microsomes. Acetaminophen-UGT activity was assayed as described previously (von Moltke et al, 1993;Court and Greenblatt, 1997a). All other assays were similar to that described for serotonin-UGT with the following relevant differences.…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro UGT activity assay using oxazepam as substrate was developed based on methods previously used in this laboratory (von Moltke et al, 1993;Court and Greenblatt, 1997a,b). Incubations (250 l for HLMs, 100 l for expressed UGTs) were performed at 37°C in 50 mM phosphate buffer (pH 7.5) with 5 mM MgCl 2 , 5 mM UDPGA, and (R,S)-oxazepam (10 -1000 M).…”
Section: Methodsmentioning
confidence: 99%